Bionomics of Anopheles fluviatilis and Anopheles culicifacies (Diptera: Culicidae) in Relation to Malaria Transmission in East-Central India. Issue 4 (25th March 2017) - Sahu, S. S.; Gunasekaran, K.; Krishnamoorthy, N.; Vanamail, P.; Mathivanan, A; Manonmani, A.; Jambulingam, P.
Abstract: The southern districts of Odisha State in east-central India have been highly endemic for falciparum malaria for many decades. However, there is no adequate information on the abundance of the vector species or their bionomics in relation to space and time in these districts. Therefore, a study was carried out on the entomological aspects of malaria transmission to generate such information. Collections of mosquitoes were made once during each of the three seasons in 128 villages selected from eight districts. Villages within the foot-hill ecotype had a significantly greater abundance of Anopheles fluviatilis James s. l., whereas the abundance of Anopheles culicifacies Giles s. l. was significantly greater in the plain ecotype. The abundance of An. fluviatilis was maximum during the cold season, whereas An. culicifacies abundance was highest during summer and rainy seasons. The maximum likelihood estimation of the malaria infection rate in An. fluviatilis was 1.78%, 6.05%, and 2.6% in Ganjam, Kalahandi, and Rayagada districts, respectively. The infection rate of An. culicifacies was 1.39% only in Kandhamal district; infected females were not detected elsewhere. Concurrently, the annual malaria parasite incidence (MPI) was significantly higher in hill-top (17.6) and foot-hill (14.4) villages compared to plain villages (4.1). The districts with more villages in hill-top and foot-hill ecotypes also had a greater abundance of An. fluviatilis, the major malaria vector, and exhibited a higher incidence of malaria than villages within the plain ecotype, where An. culicifacies was the most abundant vector.